Case Report: Circulating Anti-SARS-CoV-2 Antibodies Do Not Cross-React With Pemphigus or Pemphigoid Autoantigens - Kasperkiewicz, Michael; Bednarek, Marta; Tukaj, Stefan (Frontiers in Medicine, 2021)
It is hypothesized that SARS-CoV-2 has the potential to elicit autoimmunity due to molecular mimicry between immunogenic proteins of the virus and human extracellular molecules. While in silico and in vitro evaluation of such immune cross-reactivity of human antibodies to SARS-CoV-2 proteins with several different tissue antigens has been described, there is limited information specifically pertaining to the immunological effects of COVID-19 and vaccines against SARS-CoV-2 on the development of autoimmune bullous diseases (AIBDs). Twelve seropositive post-COVID-19 individuals and 12 seropositive healthy volunteers who received two doses of the mRNA COVID-19 vaccine from Pfizer-BioNTech have been included in this case series investigation. Serum samples of these blood donors were tested for autoantibodies to the main immunobullous autoantigens, i.e., desmoglein 1, desmoglein 3, envoplakin, BP180, BP230, and type VII collagen. Our study revealed that none of the 24 anti-SARS-CoV-2 IgG-positive subjects had concomitant antibody reactivity with any of the tested autoantigens. These results argue against a relationship between SARS-CoV-2 infection/vaccines and AIBDs with respect to disease-triggering antibody cross-reactivity.